Fast rigorous analysis of rectangular waveguides by optimized 2D-TLM - Akbal, Ayhan; Balik, Hasan H. (Springer-Verlag Berlin, 2006)
In this paper, The optimized 2D-TLM as been introduced and applied to rectangular waveguides which is widely used. Results obtained by using optimized 2D-TLM were compared with analytic results and shown to be accurate.
6th International Conference on Computational Science (ICCS 2006) -- MAY 28-31, 2006 -- Reading, ENGLAND